PEMBERDAYAAN MASYARAKAT MELALUI PROGRAM KELUARGA HARAPAN (PKH) DI KELURAHAN RANOTANA WERU - Jael ., Murib; Oktavianus ., Porajow; Lorraine W. Th. Sondak (Sam Ratulangi University, 2018)
This study aims to describe Community Empowerment through Hope Family Program in Ranotana Weru Village, Wanea Sub-district, Manado City. The data collected consists of primary and secondary. The data used in this study is qualitative, by selecting the village head, the head of the environment, the accompaniment of the Hope Family Program and the beneficiaries as informants. The results of this study prove that, the empowerment done by the government to the poor in Ranotana Weru Village is very good in terms of household needs, health and education. Based on the results of this study can be concluded that; The recipient of the Hope Family Program in Kelurahan Ranotana Weru consists of eight families. Assistance in the form of Direct Cash Assistance to participants maintains the life of basic needs of the household. Community Empowerment through Family Hope Program in Kelurahan Ranotana Weru is not right on target from the main goal of Family Hope Program. Because the benefits by participants of Family Hope Program in ranotana weru sub-district mostly use is household basic need compared to education and health.